INVESTIGATION OF ELECTRIC AND THERMAL PROPERTIES OF ALKALI-ACTIVATED ALUMINOSILICATES WITH A CNT ADMIXTURE - Oldrich Zmeskal; Lucie Trhlikova; Pospisil Jan; Fiala Lukas; Florian Pavel (Ceramics-Silikáty, 2020)

(untitled)
The paper is focused on measurements of electric and thermal properties of alkali-activated aluminosilicates (AAAs) with a carbon nanotube (CNT) admixture. Such composites, fabricated from blast-furnace slag, quartz sand, water glass as an alkali activator, a small amount of electrically conductive CNT admixture and water exhibit better electric and thermal properties than the reference material without the CNT. Such an enhancement opens new practical applications, such as designing snow-melting, de-icing or self-sensing systems that do not need any external sensors to detect the current condition of the building's materials. Moreover, the economic aspect is more favourable in the case of AAA than that of Portland cement-based materials. The DC (direct current) electric properties are determined experimentally from the current-voltage (I-V) characteristics, the dielectric properties by means of impedance spectroscopy. Dielectric measurements allow us to determine the contribution of the individual components to the conductivity of the composite. The electric and thermal conductivities in the transverse direction were 16.16 μS/m and 0.907 W.m-1K-1 for 0 % of CNT and 34.46 μS/m and 1.298 W.m-1K-1 for 0.4 % of CNT, respectively